Presentation and canonical commentary on the circular letter guidelines for the management of goods - Campo Ibáñez, S.J., Miguel (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2016)
In this paper I present and comment the recent circular letter Guidelines for the management of goods, of the Congregation for Institutes for Consecrated Life and Societies of Apostolic Life, August 2, 2014. In the present document the Congregation invites the Institutes to reconsider the charisma as an inspiring element and an evaluating tool of their patrimonial management. The Letter demands the Institutes to adopt the finest tecnical tolos, in particular balances, even the audited ones, to achieve an effective, efficient and transparent management. Of a special importance are the declarations of the Letter relating to the reception of the concept of «stable patrimony of the juridical person». Finally, and as a basic tool to achieve those goals, encourages to carry out the suitable formation programs at all the levels.
Keywords: Institute for Consecrated life; Society of Apostolic Life; administration of the ecclesiastical goods; charisma; balance; audited balance; planning; transparency; efficacy; efficency.